Functional iron blockade in chronic stress and neurodivergence: a perspective on adaptive stress physiology - Hauck, Simone (Frontiers in Psychiatry, 2025)
Burnout and trauma are often framed as psychosocial conditions or as dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis. Yet across more than two decades of clinical observation, I have repeatedly encountered a recurring metabolic signature that does not fit existing frameworks: persistent hyperferritinemia without hemochromatosis or overt inflammation, coexisting with low dehydroepiandrosterone-sulfate (DHEA-S) and preserved but gradually declining cortisol dynamics. This constellation is frequently observed in neurodivergent individuals and their families, with early signs already visible in childhood as mild anemia, elevated ferritin, low vitamin D, and behavioral hypervigilance. I propose that this pattern reflects a functional iron blockade (FIB), in which low-grade interleukin-6 signaling upregulates hepcidin, degrades ferroportin, and traps iron intracellularly. While protective against oxidative stress by reducing labile Fe²+, the adaptive cost is functional iron deficiency, impaired mitochondrial efficiency, refractory fatigue, and cognitive rigidity. Recognizing this mechanism may refine the understanding of stress-related fatigue and autistic burnout, prevent misdiagnosis as hemochromatosis or incidental hyperferritinemia, and guide research into integrative pathways linking iron metabolism, vitamin D status, and HPA dynamics. This perspective highlights FIB as a potential adaptive but costly response of stress physiology, disproportionately affecting neurodivergent phenotypes.